2020
DOI: 10.3390/toxins12090561
|View full text |Cite
|
Sign up to set email alerts
|

Insight into Unprecedented Diversity of Cyanopeptides in Eutrophic Ponds Using an MS/MS Networking Approach

Abstract: Man-made shallow fishponds in the Czech Republic have been facing high eutrophication since the 1950s. Anthropogenic eutrophication and feeding of fish have strongly affected the physicochemical properties of water and its aquatic community composition, leading to harmful algal bloom formation. In our current study, we characterized the phytoplankton community across three eutrophic ponds to assess the phytoplankton dynamics during the vegetation season. We microscopically identified and quantified 29 cyanobac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 94 publications
(113 reference statements)
2
30
0
Order By: Relevance
“…Comparing the precursor m / z values and previous molecular networks available in the literature, we putatively identified the metabolites in clusters 1 and 2 as micropeptins or cyanopeptolins. 14 , 15 Node 1019 and 1005 showed high ion counts in mass spectrometry analysis and were abundant in the high-performance liquid chromatography (HPLC) profile, and these metabolites were targeted for isolation (cf. Figures 2 , S4, and S5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Comparing the precursor m / z values and previous molecular networks available in the literature, we putatively identified the metabolites in clusters 1 and 2 as micropeptins or cyanopeptolins. 14 , 15 Node 1019 and 1005 showed high ion counts in mass spectrometry analysis and were abundant in the high-performance liquid chromatography (HPLC) profile, and these metabolites were targeted for isolation (cf. Figures 2 , S4, and S5 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, cyanoprokaryotes can produce also some different from “standard” cyanotoxins alkaloids (e.g., nostodione—Nd) and specific cyanopeptides (CNPs), including NRPs, polyketides (PKs) and their hybrids (NRPs/PKs) [ 59 , 60 ]. Some of them are common in different cyanoprokaryote genera (e.g., anabaenopeptins—Aps, cyanopeptolins—CPs), while others are specific to a single genus (e.g., oscillatorin in Planktothrix ( Oscillatoria ) [ 61 ] and cryptophycins—Crs in Nostoc ) [ 59 ].…”
Section: Main Types Of Toxic Algal Compoundsmentioning
confidence: 99%
“…However, since the beginning of the 21st century, a series of studies have demonstrated that the assessment of cyanobacterial toxicity cannot solely rely on the commonly known cyanotoxins, implying the activity of other compounds, the structure and function of which need elucidation (for details see [ 4 ]). In this regard, beyond the best studied and routinely monitored cyanotoxins from the specific group of cyclic non-ribosomally produced heptapeptides, named microcystins [ 1 , 2 , 3 ], more than six hundred other peptides or peptidic metabolites, commonly unified as cyanopeptins (CNPs), were isolated from the vast metabolite repertory of cyanoprokaryotes [ 5 , 6 , 7 , 8 ]. Despite some variations in composition and amounts, these CNPs were regularly found during CyanoHABs [ 7 ].…”
Section: Introductionmentioning
confidence: 99%